Can Islamic Banks avert Banking Crises? - Mehta, Megha (2008)
The aim of this study is to integrate the religious injunction of Islamic banking against fixed interest (ribawi) based contract with the modern literature of finance and economics to demonstrate that such a system has the potential to prevent the occurrence of a banking crisis or redress this serious threat to global financial stability. It was found that interest (riba) plays a relatively major role in making the banking systems fragile and prone to crisis. The study, which is purely conceptual, concluded that contracts such as Mudharabah which are based on Islamic principles can aid in minimizing defaults within the banking system due to its unique feature of profit-sharing, and thus, assist in averting severe banking crisis situations. However, it can be argued that the present Mudharabah contracts need to be redesigned or financially engineered in light of modern finance and economics which can act as efficient shock absorbers in the banking system and reduce the fiscal costs of banking crises.